EU DEFORESTATION REGULATION AND PALM OIL: ENVIRONMENTAL PROTECTION OR NON-TARIFF BARRIER? - Decinthya Maharani (Jurnal Paradigma Hukum Pembangunan, 2025)
The EU Deforestation Regulation (EUDR) requires all European Union–based companies to ensure that their imports and exports are free from deforestation and that human rights are upheld throughout their international supply chains, including with respect to palm oil commodities. The palm oil industry, which is closely associated with deforestation issues, is the most affected by the enactment of the EUDR. The issuance of the EUDR is therefore regarded as a form of non-tariff barrier imposed by the European Parliament to protect domestic products from competition with palm oil commodities. The EUDR may be considered as a form of green protectionism or a green barrier applied by the European Union under the pretext of environmental protection, specifically deforestation arising from oil palm plantation expansion in forest areas. Indonesia, as the world’s largest producer of palm oil, has undertaken various measures to address deforestation, including through regulatory frameworks such as the Indonesian Sustainable Palm Oil (ISPO) certification, the Roundtable on Sustainable Palm Oil (RSPO), and other national regulations. Numerous efforts have been advanced in response to the issuance of the EUDR, which is discriminatory in imposing unfair rules or requirements on products from certain countries. Diplomatic engagement with the European Union continues, in coordination with like-minded countries, with the objective of seeking solutions to the divergence of views arising from the implementation of the EUDR.